Hubungan Nilai Trombosit dengan Derajat Keparahan Berdasarkan Manifestasi Klinis Demam Berdarah Dengue di Puskesmas Gending - Ummi Sya’idah; Achmad Kusairi; Ro’isah Ro’isah (STIKes Ibnu Sina Ajibarang, 2025)
Dengue hemorrhagic fever (DHF) is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito, and it is often found in children aged 2-10 years. One of the factors causing Dengue Hemorrhagic Fever is a decrease in platelet values. This study aims to analyze the correlation between platelet values ​​and severity based on clinical manifestations of Dengue Hemorrhagic Fever at the Gending Health Center. The type of research was correlational analytic with Cross Sectional Design. The population was 44 respondents. The sample used Dengue Hemorrhagic Fever patients by Accidental Sampling. The instrument used is an observation sheet to measure platelet values ​​with the severity of Dengue Hemorrhagic Fever. Data was analysed with One Way Anova Test. The results of the study obtained platelet values, namely the mean value of 150,454.60, the median value of 151,999.60, the mode value of 152,000, the minimum value of 60,000, the maximum value of 182,000. The degree of severity based on the clinical manifestations of Dengue Fever, the majority of patients were grade 2, namely 26 patients (59.1%). Analysis test using one way anova test obtained p value = 0.000 with a significant value of p value <α = 0.005 which means there is a correlation between Platelet Values ​​and the Degree of Severity Based on Clinical Manifestations of Dengue Fever at the Gending Health Center. Normal platelet values ​​can also be high and low platelet values ​​can also be low due to other factors, namely age, gender, weight and immune factors.